Narrow banking reconsidered: The functional approach to financial reform - Ronnie J. Phillips (Levy Economics Institute of Bard College, 1995)
The functional approach to reforming the financial system advocates the structural separation of the depository and lending functions of banks. As a result of such a separation, monetary and credit policy undergo a parallel separation, and government supervision and regulation of the banking industry are modified. The policy prescription developed within this approach is narrow banking, the creation of separate monetary and financial service companies with the elimination of or a substantial reduction in deposit insurance. Narrow banking not only meets the safety and soundness goals of bank regulation, but also maintains an institutional structure that accommodates market forces and technological innovation. The author recommends the creation of monetary service companies that would serve strictly a payments function and would hold only safe assets and the establishment by the federal government of a mutual fund that holds only government securities as assets.
Keywords: 330